2013
DOI: 10.1097/mog.0b013e32835ab29a
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in infection and intestinal immunity

Abstract: Purpose of Review Inflammatory bowel diseases (IBDs; e.g. Crohn’s disease and ulcerative colitis) are thought to be a consequence of an uncontrolled inflammatory response against luminal antigens, including commensal bacteria. The observed link between eosinophil levels and severity and remission rates in IBD has led to speculation that eosinophils may contribute to the antimicrobial inflammatory response in IBD. Recent Findings Eosinophils express the necessary cellular machinery (innate immune receptors, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 117 publications
(113 reference statements)
3
69
0
Order By: Relevance
“…For example, eosinophil‐derived TGF‐β is linked to tissue remodeling and induction of the extracellular matrix protein periostin in patient biopsy specimens which increases eosinophil infiltration in the mucosal layer, thus facilitating disease pathogenesis 26, 27. Furthermore, as indicated above, granule proteins such as eosinophil cationic protein, Epx, and major basic protein released by activated eosinophils during inflammation can contribute to tissue damage (alter barrier function) and dysfunction (diarrhea with bleeding) 9, 10, 11, 12. Deficiency of eotaxin‐1, the eosinophil‐specific chemokine, or blockade of its receptor (CCR3) resulting in depletion of eosinophils has been shown to attenuate inflammation in experimental models of IBD,9, 28 thus supporting the overall importance of eosinophil involvement in EGID.…”
Section: Discussionmentioning
confidence: 99%
“…For example, eosinophil‐derived TGF‐β is linked to tissue remodeling and induction of the extracellular matrix protein periostin in patient biopsy specimens which increases eosinophil infiltration in the mucosal layer, thus facilitating disease pathogenesis 26, 27. Furthermore, as indicated above, granule proteins such as eosinophil cationic protein, Epx, and major basic protein released by activated eosinophils during inflammation can contribute to tissue damage (alter barrier function) and dysfunction (diarrhea with bleeding) 9, 10, 11, 12. Deficiency of eotaxin‐1, the eosinophil‐specific chemokine, or blockade of its receptor (CCR3) resulting in depletion of eosinophils has been shown to attenuate inflammation in experimental models of IBD,9, 28 thus supporting the overall importance of eosinophil involvement in EGID.…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils secrete many cytotoxic granule proteins that have been identified as effector molecules responsible for many of the eosinophil actions in human system. The four major eosinophil granule proteins, major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil derived neurotoxin (EDN) and eosinophil peroxidase have been shown to be involved in a number of eosinophil associated functions [13]. EDN possess antiviral activity against single stranded RNA viruses like respiratory syncytial virus, Hepatitis and HIV, whereas ECP and MBP exhibit antibacterial, antiparasitic and antiviral activities.…”
Section: Increasing the Functional Abilities Of Eosinophils By Ipscsmentioning
confidence: 99%
“…Lampinen et al demonstrated that the inflammatory process in IBD involves many inflammatory cells, such as lymphocytes, macrophages, mast cells, neutrophils, and eosinophils. They indicated that eosinophils are proinflammatory agents thus producing effects such as inflammation, tissue destruction, formation of fibrosis 29,30 . Our results showed colonic wall recovery after treatment of hyperhomocyseinemic rats with crude extract of Helix aspersa compared to experimental control.…”
Section: Fig 5: Photomicrographs Of Colon Sections Of Rats Stained Wmentioning
confidence: 99%